ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN UPAH MINIMUM KABUPATEN TERHADAP KETIMPANGAN PENDAPATAN DI DALAM PROVINSI JAMBI - Wulandari, Dinda Ayu; Zulgani Zulgani; Erni Achmad (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the impact of economic growth and district/city minimum wages on income inequality in Jambi Province during the 2019–2023 period. The method employed is panel data regression using the fixed effect model approach, with the aid of EViews software. The results show that economic growth has no significant effect on income inequality, while minimum wages have a positive and significant effect. This finding suggests that increases in minimum wages may actually exacerbate inequality, as the benefits are mostly felt by workers in the formal sector, while those in the informal sector do not experience the same advantages. These results highlight the importance of inclusive policies that go beyond wage increases, focusing instead on equitable development, empowerment of micro, small, and medium enterprises (MSMEs), and improved access to education and healthcare services.